Multi-scenario location-allocation in decision-making for improving educational facility services in Kupang City - Tallo, Amandus Jong; Alraouf, Ali A.; Wibowo, Caesaryo Arif (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Regional development is inseparable from the support of education facilities. Spatial disparities in education facilities' service scales occur unevenly in the Kupang city administration. Overlaying several thematic maps with Location-Allocation analysis provides a development scenario for placing education facilities. Secondary data in the form of the distribution of existing educational facilities, consisting of elementary schools, junior high schools , and senior high schools derived from Kupang City's Regional Spatial Plan (RTRW) data, road network and building distribution obtained based on Open Street Map (OSM) publications. Comparing the overall parameters, it can be recommended that the most efficient scenario that has the least positive impact and the least negative impact is the scenario with ¼ of the optimal number of new facilities for elementary and junior high schools, while for senior high schools there needs to be further consideration between the scenario with the optimal number and the scenario with ¼ of the optimal number of new facilities in Kupang City.